Macroeconomic costs of gender gaps: the case of Mexico - David Cuberes; Marc Teignier (Ensayos Revista de Economía)
This paper uses the framework of Cuberes and Teignier (2018) to study the quantitative effects of gender gaps in entrepreneurship and workforce participation in Mexico. The focus on one specific country allows us to have detailed information on men and women’s participation in household production and their productivity in that sector. In line with our previous research, the occupational choice model predicts substantial losses in the country’s income per capita. Gender gaps in the Mexican labor market, especially in labor force participation, represent a 22% fall in total output. Market output drops by 26.5%, while household output experiences a five-fold increase. The presence of the large gap in labor force participations implies that it is important to introduce the household sector into the model to take the production that takes place outside the market sector into account.